15‐Hydroperoxy‐PGE2: Intermediate in Mammalian and Algal Prostaglandin Biosynthesis. (23rd October 2019) - Jagusch, Hans; Werner, Markus; Werz, Oliver; Pohnert, Georg
Abstract: Arachidonic‐acid‐derived prostaglandins (PGs), specifically PGE2, play a central role in inflammation and numerous immunological reactions. The enzymes of PGE2 biosynthesis are important pharmacological targets for anti‐inflammatory drugs. Besides mammals, certain edible marine algae possess a comprehensive repertoire of bioactive arachidonic‐acid‐derived oxylipins including PGs that may account for food poisoning. Described here is the analysis of PGE2 biosynthesis in the red macroalga Gracilaria vermiculophylla that led to the identification of 15‐hydroperoxy‐PGE2, a novel precursor of PGE2 and 15‐keto‐PGE2 . Interestingly, this novel precursor is also produced in human macrophages where it represents a key metabolite in an alternative biosynthetic PGE2 pathway in addition to the well‐established arachidonic acid‐PGG2 ‐PGH2 ‐PGE2 route. This alternative pathway of mammalian PGE2 biosynthesis may open novel opportunities to intervene with inflammation‐related diseases. Abstract : Ein neuer Biosyntheseweg für einen lange bekannten Lipidmediator, PGE2, wurde in der Rotalge Gracilaria vermiculophylla entdeckt (siehe Bild oben). Durch eine neuerliche Studie der Biosynthese des entzündungsvermittelnden Hormons in Makrophagen wurde dieser alternative Weg über intermediäres 15‐Hydroperoxy‐PGE2 auch in Säugern etabliert.